Binge Eating Disorder and Obesity - Diaz Lazo, Anibal (2019)
Obesity is a public health problem that increases progressively over the years, and its etiology is considered an important factor in the disordered eating habits of the population. In most cases In most cases, poor eating habits begin in childhood or adolescence (1,2). The demographic and family health survey (ENDES) conducted in 2014 in Peru, reports an overall prevalence of overweight of 33.8% and obesity of 18.3% in people over 15 years of age, being higher in coastal cities compared to what is reported in the jungle and highlands.